Effective educator-student relationships in nursing education to strengthen nursing students' resilience - Kathleen Froneman; Emmerentia du Plessis; Magdelene P. Koen (AOSIS, 2016)
Background: Little research has been conducted in private nursing schools with regard to the educator-student relationship to strengthen the resilience of nursing students and to improve the educator-student relationship. An effective educator-student relationship is a key factor to ensure a positive learning climate where learning can take place and resilience can be strengthened. Purpose: The purpose was to explore and describe nursing students' view on the basic elements required for an effective educator-student relationship to strengthen their resilience and the educator-student relationship. Method: This study followed an explorative, descriptive and contextual qualitative design in a private nursing education institution in the North West Province. Purposive sampling was used. The sample consisted of 40 enrolled nursing auxiliary students. The World Café Method was used to collect data, which were analysed by means of content analysis. Results: The following five main themes were identified and included: (1) teaching-learning environment, (2) educator-student interaction, (3) educator qualities, (4) staying resilient and (5) strategies to strengthen resilience. Conclusion: Students need a caring and supportive environment; interaction that is constructive, acknowledges human rights and makes use of appropriate non-verbal communication. The educator must display qualities such as love and care, respect, responsibility, morality, patience, being open to new ideas, motivation, willingness to 'go the extra mile' and punctuality. Students reported on various ways how they manage to stay resilient. It thus seems that basic elements required in an effective educator-student relationship to strengthen the resilience of students include the environment, interaction, educator and student's qualities and resilience. Keywords: Educator-student relationship, nursing education, nursing education institution (NEI), nursing student, learning environment, resilience